PENGARUH STRATEGI BAURAN PEMASARAN PARIWISATA TERHADAP KEPUASAN WISATAWAN DENGAN FEELING SEBAGAI VARIABEL MEDIASI (studi pada pemasaran pariwisata berbasis alam, budaya dan warisan etnis di Kota Pontianak) - B11110116, REZZA PRIBADI ARHAM (Jurnal Manajemen Update, 2015)
This study aimed to determine the impact of service marketing mix consisting of products, price, promotion, place, people, process, and physical evidence on consumer satisfaction through feeling as mediating variable. This research used descriptive study design. The population of this study was the tourists visiting Pontianak city who are at least 17 years old. The sampling method was accidental sampling in which the study involved 100 tourists in Pontianak city. The study used path analysis with SPSS 17. The finding of the study showed that product (X1), process (X6), and physical evidence (X7) have significant effect on feeling (Y1). Similarly, physical evidence (X7) and feeling (Y1) have significant effect on tourist satisfaction (Y2). The variable of feeling (Y1) acts as variable that mediates the effect of variable of price (X2), place (X4), people (X5), process (X6), and physical evidence (X7) on tourist satisfaction (Y2), but it does not act as variable that mediates the effect of variable of product (X1) and promotion (X3) on tourist satisfaction (Y2). Keywords : service marketing mix, product, price, promotion, place, people, process, physical evidence, feeling and tourist satisfaction.